TEKNOLOGI PEMUPUKAN PADA TANAMAN JAMBU METE - Usman Daras; Maman Herman; Sakiroh Sakiroh (Jurnal Tanaman Industri dan Penyegar, 2011)
Cashew (Anacardium occidentale Linn) is among the leading export crops in Indonesia. It is also animportant smallholder crop mainly grown in the eastern parts of Indonesia. Its expansion of growing the crop, it is however n ot followed by significant increases in yields, being low ranging of 200 – 350 kg/ha. Many factors believed affect yields achieved, begun from environment, cultivatedvarieties, up to poor management of cashew orchard. As the cashew trees are mostly developed in marginal lands, role of ferti lizer uses may become exeedingly important effort in improving the productivity of the crops. In addition, there are many evidences that the crops adequately managed may give better in yields. However, most farmers do not use fertilizers for the crops or if any, added in very small amounts obviously addressed for annual crops like maize, bean or rice usually planted among the cashew trees. As results, the cashew trees are not able to achieve opti mum yields even though the planting materials used might have high in yield potential. The fertilizers that may be used both in form of organic and inorganic ones. They should be added in such way, so the soils on which the crops are planted be able to grow and develop well, in turn, their yields increase significantly.